解{3x+4y=-3,2x-3y=-2
来源:学生作业帮助网 编辑:六六作业网 时间:2025/02/03 21:44:44
解{3x+4y=-3,2x-3y=-2解{3x+4y=-3,2x-3y=-2解{3x+4y=-3,2x-3y=-2(1)×3+(2)×4得17x=-17∴x=-1把x=-1代入(1)得-3+4y=-3
解{3x+4y=-3,2x-3y=-2
解{3x+4y=-3,2x-3y=-2
解{3x+4y=-3,2x-3y=-2
(1)×3+(2)×4得
17x=-17
∴x=-1
把x=-1代入(1)得
-3+4y=-3
y=0
∴x=-1
y=0
x=-1 y=0
(x-y) (x-2y)+(x+2y) (x-3y)-2(x-3y) (x-4y)=
2(x+y)-3(x-y)=3 ,4(x+y)+3(x-y)=15
x+y/2+x-y/3=6,4(x+y)-3(x-y)=-20
{(x+y)/2+(x-y)/3=6 4(x+y)-3(x-y)=-20
4(x+y)-3(x-y)=-20,2/x+y+3/x-y=6
3(x+y)-2(x-y)=11 4(x+y)+3(x-y)=9
3(x+y)+2(x-y)=36 4(x+y)-5(x-y)=2
(x+y)/2- x-y/2=6 3(x+y)=4(x-y)
x+y/3+x-y/2=6 4(x+y)-2(x-y)=40
{3(x+y)-4(x-y)=4 {x+y/2 + x-y/6=1
4(x-y)-3(x-y)=9 5(x-y)+2(x-y)=11
3(x+y)-4(x-y)=11,2(x-y)+5(x+y)=27
解二元一次方程组:3(x+y)-4(x-y)=4,x+y/2+x-y/6+1x+y/2+x-y/6+1=1
先化简再求值(x-y)(x-2y)+(x-2y)(x-3y)-2(x-3y)(x-4y) x=4 y=5
(x+y)(x-y)+(x-y)平方-(x-y)(3x-y) 其中x=-2 y=3分之一
已知x-y/x+y=3,求代数式5(x-y)/x+y-x+y/2(x-y)
已知2y-x=-3,求[4y(2x-y)-2x(2x-y)]/(2x-y
x+y+2(-x-y+1)=3(1-y-x)-4-(y+x-1),x+y=?